(untitled) (IJOVTECH, 2026)
With the emergence of blockchain technology, especially with smart contracts, different industries, including finance, have been transformed by improving their transparency, security, and performance. This paper examines the potential of smart contracts through blockchain technology on the financial reporting and efficiency in audit in the context of Ebonyi State, Nigeria, which experiences both innovating financial systems and regulatory compliance issues. Based on the primary data gathered among 250 respondents (that is, accountants, auditors, and financial managers in Ebonyi State, both in the state and in a particular entity) the research uses a mixed-methods approach to gauge the barriers to adoption, perceived benefits, and improvements in operations. The theoretical framework incorporates the Transactions Cost Theory and Technology Acceptance Model to establish how smart contracts minimize transaction costs and help in making users accept the auditing process. Results indicate that implementation of smart contracts has the potential to cut audit time by up to 40 percent, and decrease audit mistakes in financial reporting by 35 percent, according to survey outcomes and statistical tests. Nonetheless, in Ebonyi State, it is impeded by lack of technological infrastructure, regulatory loopholes, and man skills. Among the demographic factors emphasized in the study, the sample age is mainly between 35-50 (62%), bachelor degree (58%), and small-to-medium enterprises (45%). These results are endorsed by the existing literature and focus on the use of blockchain in unchanging registers to prevent fraud and to perform real-time verification. Policy reforms needed in integration of blockchain in Nigerian financial standards and training programs based on local needs have been recommended. This study makes a contribution to the business management literature by presenting empirical data in a relatively underrepresented African setting, underlining the possibility of blockchain functioning to remove the lack of efficiency in emerging markets.